Radon Gas Profiles and Exposure Estimates in the Perama Cave, Greece - Papachristodoulou, C. A.; Ioannides, K. G.; Stamoulis, K. C.; Patiris, D. L.; Pavlides, S. B. (HNPS Advances in Nuclear Physics, 2020)
An investigation of atmospheric radon levels in the Perama Cave, North-western Greece, has been carried out using CR-39 detectors. The detectors were placed at various locations along the guided cave pathway and exposed during different sampling periods. Mean concentrations amounting to 925±418 and 1311±352 Bq m-3 were recorded in the summer and winter months, respectively. The quantification of effective doses from radon daughters' inhalation was important, as the Perama Cave is one of the most popular in Greece, attracting more than 85,000 tourists per year. Due to the short duration of the guided tour along the cave, exposure of tourists was found to be insignificant, lying below 5.1 μSv per visit. Permanent cave guides receive doses ranging from 4.2 to 5.9 mSv y-1. Considering the ICRP-65 recommendation that action levels in dwellings and workplaces should be set between 3 and 10 mSv y-1 untertaking remedial measures to reduce the exposure of cave staff may be appropriate.